Peranan Orang Tua dalam Menanamkan Nilai-Nilai Agama Islam untuk Menanggulangi Pergaulan Bebas pada Remaja di Desa Lumpo Kecamatan IV Jurai Kabupaten Pesisir Selatan - Aldi Setiawan; Muhammad Yusuf (YASIN, 2026)
The issue of adolescent promiscuity has received considerable scholarly attention, yet studies that specifically examine the role of parents in instilling Islamic religious values as an effort to address adolescent promiscuity in the context of religious rural communities remain relatively limited. This study aimed to analyze the parental role, parents’ strategic position, and the obstacles they face in instilling Islamic religious values to counter adolescent promiscuity in Lumpo Village, IV Jurai Subdistrict, Pesisir Selatan Regency. A qualitative approach with a case study design was employed, involving parents of adolescents, adolescents themselves, as well as community and religious leaders selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings show that parents play a role in instilling Islamic religious values through providing religious advice, habituating worship practices, modeling appropriate behavior, and monitoring adolescents’ social interactions. Parents occupy a central position as the primary controllers of adolescent behavior; however, the effectiveness of this role is influenced by the quality of interaction and communication within the family. The study also identifies several obstacles, including parents’ limited time, the influence of peer social environments, and the rapid development of technology and social media. These findings contribute to the development of family education theory in Islam and role theory by deepening understanding of parental roles in religious rural communities, while underscoring the importance of parental consistency and role modeling as well as synergy among families, communities, and educational institutions in addressing adolescent promiscuity.